An Analysis of Teachers’ Strategies in Teaching Reading Comprehension at Tenth Grade Students of Vocational High School 2 Malang - Anis Rahmawati Khusnul Chotimah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
This study aimed to provide teachers’ strategies in teaching reading comprehension conducted by the English teacher of tenth grade of Vocational High School 2 Malang. This study used a descriptive qualitative research. The researcher chose one of the senior English teachers of Vocational High School 2 Malang who had good quality in teaching English, especially reading comprehension. In addition, to obtain the data, the researcher used observation and interview as the main instruments, and some supportive instruments such as document. The finding of the study indicated that the observed teacher used some certain platforms to maximize the teaching reading comprehension. The observed teacher also divided the activities into three steps, namely in pre-reading activities, during-reading activities, and post-reading activities and implemented various activities to the students either using Mclass, Google Classroom, Live Worksheet, ISL Collective, Youtube, WhatsApp Mesengger, and Google Meet. The researcher found out that the observed teacher applied (QARs) Question Answer Relationship and meta-cognitive strategy in teaching reading comprehension. The teachers used these strategies to make students understand the reading text and guide students to more focus on the text. Besides, teacher could help students in developing the meaning contained in the reading text so that students more easily understand the content of the reading. Keywords: Teacher strategies; teaching reading